Mechanical design, analysis and development of deployment mechanism for cubesat SAR S-band membrane antenna - Divya Agarwal (Nanyang Technological University, 2020)
The need for large antennas in the aerospace industry has spurred research into deployable membrane antennas, due to their lightweight and compact storage capacity. One of the main problems of incorporating large antennas in small satellites is the packaging and safe deployment of structural booms and membranes. The goal of a researcher in this field would be to enhance deployable boom predictability and ground testability, develop design that are tolerant of manufacturing imperfections, and get reliable and simple deployment methods. This study aims to mechanically design, analyze and develop a deployable boom mechanism for an S-band planar membrane antenna. The design must fulfill the desired structural requirements, aiming to achieve large apertures with reduced stowage volume and low mass budget. To perform the preliminary antenna boom design, a trade off among the concepts of deployment devices available in the literature was conducted and a suitable concept was chosen, through a simplified analytical hierarchy process. A matrix of space-qualified material was created, and the right material was selected based on a criterion that gave a low density and high stiffness material. The boom length was among the principle requirements of this study. Accordingly, static, modal, and harmonic analyses necessary to assess the requirements and choose the boom secondary dimensions were executed via a finite element model. Two designs were generated: concept A (tape spring) and concept B (telescopic boom). The former, which is more innovative, met all the criteria except stiffness and rigidity. The latter approach, which is more conservative, is relatively heavier and does not fit into the small volume of satellite. However, it provides better stiffness and can be optimized to meet the specified requirements. The novelty of this study is that it uses a stacer. Instead of a belt for the deployment, which, to the best of the author’s knowledge, is unique.